Developmental effects of PFOS, PFOA and GenX in a 3D human induced pluripotent stem cell differentiation model. (September 2021) - Davidsen, Nichlas; Rosenmai, Anna Kjerstine; Lauschke, Karin; Svingen, Terje; Vinggaard, Anne Marie
Abstract: Polyfluoroalkyl substances (PFASs), including perfluorooctanesulfonic acid (PFOS) and perfluorooctanoic acid (PFOA), are persistent pollutants routinely found in human blood. PFASs have been associated with health issues such as decreased birth weight and impaired vaccination response in children. Substitutes to these PFASs, such as ammonium 2, 3, 3, 3-tetrafluoro-2-(heptafluoropropoxy)propanoate (GenX) have been introduced, although hazard information is limited. Human induced pluripotent stem cell (hiPSC) based models are valuable for studying these compounds, as they mimic human embryonic development. We used our recently developed PluriBeat assay to investigate PFOS, PFOA and GenX for effects on early embryonic development in vitro. In our assay hiPSCs go through the early stages of embryonic development in 3D cultures of embryoid bodies (EBs) that mimic the human blastocyst until they finally form beating cardiomyocytes. Both PFOS and PFOA had a strong effect on cardiomyocyte differentiation at non-cytotoxic concentrations, with PFOS being more potent than PFOA. Moreover, both compounds decreased EB size at the highest test concentrations. GenX induced a weak concentration-dependent effect on differentiation of one hiPSC line, but not of another. Transcriptional analysis of mRNA from the cardiomyocytes showed that PFOS increased expression of the early cardiac marker ISL1, whereas PFOA decreased expression of the cardiomyocyte marker MYH7 . This suggest that PFOS and PFOA perturb cardiomyocyte differentiation by disrupting molecular pathways similar to those taking place in the developing embryo. Based on these findings, we conclude that our PluriBeat assay has the potential to become a valuable, sensitive model system for elucidating embryotoxic effects of PFASs in future. Graphical abstract: Image 1 Highlights: Developmental toxicity of PFOS/PFOS/GenX was tested in a human stem cell assay. PFOS and PFOA inhibited cardiomyocyte development with increasing concentrations. Gene expression of ISL1 and MYH7 was affected by PFOS and PFOA, respectively. Our results may hint at a mechanism, whereby PFAS disrupt embryonic development.